A Globally Convergent Hybrid Conjugate Gradient Method and Its Numerical Behaviors - Yuan-Yuan Huang; San-Yang Liu; Xue-Wu Du; Xiao-Liang Dong (Journal of Applied Mathematics)
We consider a hybrid Dai-Yuan conjugate gradient method. We confirm that its numerical performance can be improved provided that this method uses a practical steplength rule developed by Dong, and the associated convergence is analyzed as well.